Dissemination of high-risk clones of extensively drug-resistant pseudomonas aeruginosa in Colombia (2020)
The ability of Pseudomonas aeruginosa to develop resistance to most antimicrobials represents an important clinical threat worldwide. We report the dissemination in several Colombian hospitals of two predominant lineages of extensively drug-resistant (XDR) carbapenemase-producing P. aeruginosa strains. These lineages belong to the high-risk clones sequence type 111 (ST111) and ST235 and harbor blaVIM-2 on a class 1 integron and blaKPC-2 on a Tn4401 transposon, respectively. Additionally, P. aeruginosa ST1492, a novel single-locus variant of ST111, was identified. Clonal dissemination and the presence of mobile genetic elements likely explain the successful spread of XDR P. aeruginosa strains in Colombia.